A Survival Analysis of Adolescent Friendships: The Downside of Dissimilarity. (August 2015) - Hartl, Amy C.; Laursen, Brett; Cillessen, Antonius H. N.
The present study examined whether adolescent friendships dissolve because of characteristics of friends, differences between friends, or both. Participants were 410 adolescents (201 boys, 209 girls; mean age = 13.20 years) who reported a total of 573 reciprocated friendships that originated in the seventh grade. We conducted discrete-time survival analyses, in which peer nominations and teacher ratings collected in Grade 7 predicted the occurrence and timing of friendship dissolution across Grades 8 to 12. Grade 7 individual characteristics were unrelated to friendship stability, but Grade 7 differences in sex, peer acceptance, physical aggression, and school competence predicted subsequent friendship dissolution. The findings suggest that compatibility is a function of similarity between friends rather than the presence or absence of a particular trait.